Handroanthus heptaphyllus (Martius) Mattos response in different volumes of substrate and base fertilization - TONETTO, Thaise da Silva; Araujo, Maristela Machado; Berghetti, Álvaro Luís Pasquetti; Navroski, Márcio Carlos (Floresta, 2020)
Handroanthus heptaphyllus (Martius) Mattos response in different volumes of substrate and base fertilization. The native forest species require the adoption of appropriate practices in the nursery, such as the definition of the container volume and base fertilizer, to develop seedlings at lower cost. Thus, this study aimed to verify the performance of Handroanthus heptaphyllus seedlings grown in nurseries in different sizes of containers and different dosage of controlled release fertilizer (CRF). There was interaction between the volume of container and the fertilization for the height (H), stem diameter (SD), and H/SD relation. The shoot dry mass variable (SDM), root dry mass (RDM), total dry mass (TDM), SDM/RDM relation, Dickson quality index (DCI) and leaf area (LA) were influenced only by the base fertilizer. The highest values for these variables were, respectively, 15.68 cm; 6.55 mm, 2.58 cm mm-1; 2.05 g; 2.03 g; 3.84 g; 1.46; 1.15 and 246.97 cm². The H. heptaphyllus species is nutritionally demanding, positively responding to the high dose of CRF. Seedlings of H. heptaphyllus produced in tubes of 180 cm³ with 7.0 g L-1 of CRF present adequate growth.